Activation of Nrf2/HO-1 Antioxidant Pathway by Heme Attenuates Calcification of Human Lens Epithelial Cells - Arpan Chowdhury; Enikő Balogh; Haneen Ababneh; Andrea Tóth; Viktória Jeney (MDPI AG, 2022)
Cataract, an opacification in the crystalline lens, is a leading cause of blindness. Deposition of hydroxyapatite occurs in a cataractous lens that could be the consequence of osteogenic differentiation of lens epithelial cells (LECs). Nuclear factor erythroid 2-related factor 2 (Nrf2) controls the transcription of a wide range of cytoprotective genes. Nrf2 upregulation attenuates cataract formation. Here we aimed to investigate the effect of Nrf2 system upregulation in LECs calcification. We induced osteogenic differentiation of human LECs (HuLECs) with increased phosphate and calcium-containing osteogenic medium (OM). OM-induced calcium and osteocalcin deposition in HuLECs. We used heme to activate Nrf2, which strongly upregulated the expression of Nrf2 and heme oxygenase-1 (HO-1). Heme-mediated Nrf2 activation was dependent on the production of reactive oxygens species. Heme inhibited Ca deposition, and the OM-induced increase of osteogenic markers, RUNX2, alkaline phosphatase, and OCN. Anti-calcification effect of heme was lost when the transcriptional activity of Nrf2 or the enzyme activity of HO-1 was blocked with pharmacological inhibitors. Among products of HO-1 catalyzed heme degradation iron mimicked the anti-calcification effect of heme. We concluded that heme-induced upregulation of the Nrf2/HO-1 system inhibits HuLECs calcification through the liberation of heme iron.